Antibacterial Evaluation of Quassia Indica (Gaertn.) Nooteb. in Steenis Towards Bacteria Involved in Skin Diseases - Kassim Ajeena P; Thomas Toji (Journal of Global Pharma Technology, 2010)
Quassia indica has been used as medication for a number of diseases in traditional systems of medicine. Leaves of Quassia indica evaluated for its antibacterial potential and phytochemical contents in various solvent extracts of the plant in increasing polarity towards pathogenic bacterial species involved in skin diseases in human beings. Antibacterial activity was evaluated by disc diffusion method. Petroleum ether and ethanol extracts were found to be active against Pseudomonas aeruginosa. The results indicated that the plant exhibited antibacterial activity especially towards single pathogen, Pseudomonas aeruginosa. Phytochemical analyses were performed to analyse the nature of compounds contained in the active extracts. Flavonoids, phenols, steroids were detected in petroleum ether and ethanol extracts. Alkaloids were not detected in any of the extracts. Active ethanol extract of the plant exhibited minimum inhibitory concentration as well as minimum bactericidal concentration of 31.25mg/ml towards Pseudomonas aeruginosa. The study revealed that the active ethanol extract possessed some antibacterial compounds, which could be isolated from the ethanol extract. Keywords: Quassia indica,Simaroubaceae, antibacterial, disc diffusion, MIC